Safe and Sustainable by Design: Driving Innovation Toward Safer and More Sustainable Chemicals, Materials, Processes and Products - Garmendia Aguirre, Irantzu; Rasmussen, Kirsten; Rauscher, Hubert (Sustainability & Circularity NOW, 2025)
The Safe and Sustainable by Design (SSbD) framework, developed by the European Commission’s Joint Research Centre, is described here. It is applicable to chemicals and materials, and the European Commission recommends its use in research and innovation activities. This framework is one means to facilitate achieving the goals of the European Union’s Chemicals Strategy for Sustainability. The implementation of the SSbD framework calls for a new way of thinking and a shift in current innovation practices. It thus requires safety and sustainability to be considered in an integrative manner from the early stages of innovation, and with a life cycle perspective. This article describes the policy context in which SSbD was developed, outlines the concepts underpinning SSbD, and its assessment steps. Furthermore, it presents some early implementation lessons learned, gives an overview of ongoing work to implement and advance its development, and provides an outlook for future developments. The transition to SSbD requires deeper integration of several disciplines, until now often independently practiced, that address chemical risk and sustainability. In addition, the implementation of these disciplines, from the early design phase of new chemicals, materials, processes, and products onward, makes the engagement of communities in the research and innovation fields paramount.
Keywords: Safe and sustainable by design; Safety; Sustainability; Innovation; Life cycle; Value chain; Integration of safety and sustainability